2019
DOI: 10.1128/jvi.00453-19
|View full text |Cite
|
Sign up to set email alerts
|

Rho-Associated Coiled-Coil Kinase 1 Translocates to the Nucleus and Inhibits Human Cytomegalovirus Propagation

Abstract: Rho-associated coiled-coil kinase (ROCK) protein is a central kinase that regulates numerous cellular functions, including cellular polarity, motility, proliferation, and apoptosis. Here, we demonstrate that ROCK has antiviral properties, and inhibition of its activity results in enhanced propagation of human cytomegalovirus (HCMV). We show that during HCMV infection, ROCK1 translocates to the nucleus and concentrates in the nucleolus, where it colocalizes with the stress-related chaperone heat shock cognate 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
(51 reference statements)
1
11
0
Order By: Relevance
“…Given that DAPK3 is a downstream substrate of ROCK 114 that positively regulates Wnt signaling, 111 it is tempting to speculate that nuclear translocation of DAPK3 contributes to this HCMV-induced increase in Wnt signaling. In support of this notion, ROCK activation has been shown to restrict HCMV propagation, 115 and ROCK is known to phosphorylate DAPK3 at a site that inhibits its nuclear localization. 114 Given our findings, it is possible that the plasma membrane to cytoplasm and nucleus translocation of DAPK3 represents a missing link in HCMV induction of Wnt signaling.…”
Section: T H I S C O N T E N T Imentioning
confidence: 92%
“…Given that DAPK3 is a downstream substrate of ROCK 114 that positively regulates Wnt signaling, 111 it is tempting to speculate that nuclear translocation of DAPK3 contributes to this HCMV-induced increase in Wnt signaling. In support of this notion, ROCK activation has been shown to restrict HCMV propagation, 115 and ROCK is known to phosphorylate DAPK3 at a site that inhibits its nuclear localization. 114 Given our findings, it is possible that the plasma membrane to cytoplasm and nucleus translocation of DAPK3 represents a missing link in HCMV induction of Wnt signaling.…”
Section: T H I S C O N T E N T Imentioning
confidence: 92%
“…Interestingly, siRNA depletion of Rock1, but not Rock2, significantly reduced EV‐A71 replication in both cell lysates and supernatant, indicating that Rock1 is a potential host factor involved in EV‐A71 replication (Figure 5). Notably, previous studies have shown that Rock1, which mainly localizes to the nucleolus, is translocated to the nucleus during human cytomegalovirus infection 46 . The results suggest that antiviral activity of Rock1 in EV‐A71 infection may be associated with activation of the actomyosin network and inhibition of capsid egress out of the nucleus.…”
Section: Discussionmentioning
confidence: 71%
“…Among the other candidate DcEntB interactors that are predicted by NoD NoLS predictor [ 33 ] to be nucleolar proteins ( S5 Table ), PES-7/IQGAP, LET-60/HRas, RAB-6.1/RAB6A and CDC-42/CDC42 all have GTP binding or GTPase activity. Interestingly, the homologue of LET-502, the Rho-associated coiled-coil kinase, ROCK1, was recently shown to concentrate in the nucleolus during human cytomegalovirus infection [ 83 ]. Whether these different candidates are authentic interactors of DcEntB remains, however, to be established.…”
Section: Resultsmentioning
confidence: 99%